Análise experimental de micromisturador tipo herringbone utilizando a técnica de fluorescência induzida por laser - Garcia, Douglas de Almeida (2019)
The fluid mixing process is present in many industrial sectors and has the most varied applications. With the advent of microfluidics, microfluidic systems, micromixers in particular, have been developed and can be applied to intensify processes that require continuous and efficient fluid mixing and low residence time, yielding better yields than the batch process of conventional ways. The present experimental study aims to analyze the mixing efficiency of two staggered herringbone micromixers (SHM), of different groove width, and compare with a straight microchannel from the characterization of the concentration field of the flow inside these microdevices. For this, the non-intrusive Microscale Laser-Induced Fluorescence (-LIF) measurement technique was used to measure the flow concentration fields. The fabrication of the microdevices was made in polydimethylsiloxane (PDMS) by the soft-lithography technique combined with the lowcost fabrication of the molds in polymethyl-methacrylate (PMMA) by the micro-milling via computational numerical command (CNC). The results obtained showed a mixing efficiency higher than 95% for the both micromixers studied in different mixing lengths for 0,5 ≤ ≤ 333 and 1,1 x 10ଷ ≤ ௠ ≤ 7,5 x 10ହ.